2011
DOI: 10.1136/jramc-157-01-18
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Blood Pressure, Arterial Stiffness and Pulse Waveform Analysis at Altitude

Abstract: We conclude that acute exposure temporarily affected endothelial function as measured by a change in vascular tone but this did not predict the development of AMS. The rise in arterial BP was not related to changes in arterial stiffness or tone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 16 publications
5
18
1
Order By: Relevance
“…In a very recently published field study (n = 17) to 4770 m, Rhodes et al failed to demonstrate a consistent change in arterial SI with high altitude exposure, but did observe an ACUTE HYPOBARIC HYPOXIA initial significant fall in RI, as in our study. However, as with all of the above studies assessment of diastolic function and PAP were not performed (Rhodes et al, 2011). Our data appears to suggest that hypoxia leads to differential haemodynamic effects along the arterial tree.…”
contrasting
confidence: 61%
See 1 more Smart Citation
“…In a very recently published field study (n = 17) to 4770 m, Rhodes et al failed to demonstrate a consistent change in arterial SI with high altitude exposure, but did observe an ACUTE HYPOBARIC HYPOXIA initial significant fall in RI, as in our study. However, as with all of the above studies assessment of diastolic function and PAP were not performed (Rhodes et al, 2011). Our data appears to suggest that hypoxia leads to differential haemodynamic effects along the arterial tree.…”
contrasting
confidence: 61%
“…The endothelium is also a principle regulator of arterial stiffness (Wilkinson et al, 2002;Boos et al, 2007). There have been very few studies that have investigated the effects of hypoxia on arterial stiffness and its relationship to endothelial function under hypoxic conditions and the findings have been inconsistent (Vedam et al, 2009;Rhodes et al, 2011). This has clinical implications as changes in arterial stiffness influence diastolic function and left ventricular (LV) filling (London et al, 2004;Chung CM et al, 2010;Erdogan et al, 2007).…”
Section: Introductionmentioning
confidence: 92%
“…In addition, systolic blood pressure also significantly increased after high-altitude exercise [6]. Significant rise in systolic and diastolic blood pressure in the initial phase of exposure to altitude was also reported in other studies [7,8].…”
Section: Cardiac Systemsupporting
confidence: 54%
“…The muscular arteries are much more sensitive than elastic arteries to sympathetic nervous system activity, and, therefore, the weak and insignificant increase in carotid-radial PWV with altitude suggests that other factors, in addition to sympathetic activation, may 26,27 hemoconcentration with consequent increase in blood viscosity, 28 and interstitial edema 29 of the arterial wall, may have an important role in determining the changes in arterial distensibility observed in this condition. Acute exposure to HA has indeed been reported to impair both endothelial 5,30 and vascular smooth muscle-cell function, 5 as shown in a previous study by our group which demonstrated a link between the altitude-induced increase in pulmonary artery pressure and an increase in plasma and urinary endothelin-1 levels. 31 All these changes might contribute to explain the hypoxia-related increase in arterial stiffness at altitude, although their possible role in this regard is mostly based on speculative considerations which remain to be supported by further experimental studies.…”
Section: Arterial Stiffness At Very Hamentioning
confidence: 62%